The Scavenger Receptor SREC-I Cooperates with Toll-Like Receptors to Trigger Inflammatory Innate Immune Responses - Murshid, Ayesha; Borges, Thiago J.; Lang, Benjamin J.; Calderwood, Stuart K. (Frontiers in Immunology, 2016)
3 SREC-I is a Class F scavenger receptor expressed by immune cells with a significant role in 4 CD8+ and CD4+-mediated T cell immunity. This receptor can also modulate the function of Toll 5 like receptors (TLR) which play essential roles in innate immunity. Here we will discuss how 65 SREC-I alters double stranded RNA (dsRNA)-mediated TLR3 activation. Earlier it was found 76 that human monocyte/macrophage THP1 cells as well as bone marrow derived macrophages 87 from mice exhibited increased responses to polyinosine-polycytidylic acid (poly I:C, PIC) and 98 CpG (unmethylated) DNA and enhanced production of inflammatory cytokines with 109 overexpressed SREC-I. Our data also showed that intracellular/endocytic TLR3 and TLR9 could 1110 directly interact with SREC-I in the presence of their respective ligands. We also observed that 1211 the internalized ligand along with TLR3/TLR9 colocalized in the endosome in macrophages and 1312 THP-1 cells over expressing these receptors. In the absence of these ligands there was no 1413 detectable colocalization between the SREC-I and endocytic TLRs. It was shown earlier that 1514 SREC-I stimulated dsRNA/CpGDNA mediated TLR3/TLR9 activation of the innate immune 1615 response by triggering signaling through the NF-κB, IRF3 and MAP kinase pathways leading to 1716 transcription of cytokine genes. We also established that SREC-I can associate with plasma 1817 membrane TLRs, like TLR2 and TLR4. We demonstrated that SREC-I-TLR4 signals more 1918 efficiently from lipid microdomain in which LPS can associate with SREC-I-TLR4 complex. We 2019 also proved that SREC-I is an alternate receptor for LPS capable of internalizing the complex 2120 and for endocytic TLR ligands as well. This binding activated endocytic TLR mediated 2221 downstream cytokine production in THP1 cells and macrophages. Finally, SREC-I could also 2322 form complexes with TLR2 and induce the release of cytokines in the presence of bacterial, viral 2423 and fungal ligands.